Complete Monotonicity Properties of a Function Involving the Polygamma Function - Kwara Nantomah (Engineering and Applied Science Letters, 2018)
In this paper, we study completete monotonicity properties of certain functions associated with the polygamma functions. Subsequently, we deduce some inequalities involving difference of polygamma functions.